The Portrayal of Apocalypse in Jules Hogan’s Those They Left Behind: An Ecocritical Analysis - Prabawati, Theresia Sekar (Universitas Sanata Dharma, 2023)
Literary works can show problems in our life, such as the ones in the relationship between human beings and nature. Through this paper, the researcher aims to find out the portrayal of the apocalypse in a short story entitled Those They Left Behind by Jules Hogan. To reveal how the apocalypse is represented, there are two problems to answer: (1) how the condition of the environment is depicted in the story and (2) how the condition affects the characters. The study is qualitative research, applying the theory of ecocriticism proposed by Greg Garrard. The tropes discussed in this research are pollution, pastoral, and apocalypse. It is found that the apocalypse happened because of the great number of pollution, the rising cases of catastrophes, and modernization. Therefore, the Ascent project was established to send human beings to start a new life on another planet. The apocalyptic state affected the characters in significant ways. They had to change their lifestyles to survive, starting from recycling waste, living from natural resources, and finding ways to reduce pollution.The short story leaves the reader with the idea that if human beings do not change their ways, the Earth will eventually be destroyed.